Analysis of The Licensing Service System in Improving The Quality of Micro, Small and Medium Enterprises Products in Maros Regency - Nurhaedah Nurhaedah; A. Arwinda Wildam; Syahrir; Muh. Dwi Ardianto (Economics and Business Journal (ECBIS), 2026)
Micro, Small and Medium Enterprises (MSMEs) are the backbone of Maros Regency's economy, with a significant development of 1,000 units to 2,000 units until December 2025, which is dominated by the culinary sector. In addition, the fisheries sector is also the focus of development with milkfish production with a production of more than 9,100 tons per year by 2024 with market potential that continues to grow in line with the Free Nutritious Meal (MBG) program involving MSMEs as suppliers. The contribution of MSMEs is not only felt in the absorption of labor and income of the local community, but also supports the tourism sector through souvenir products and services related to tourist destinations such as Bantimurung Tourism Park and Rammang-rammang Kart Area to support more sustainable growth, access to business legality and ease in the licensing process are crucial factors that need to be considered. Data collection for this study was carried out from December 1, 2025 to December 24, 2025. Respondents in this study were collected from MSME actors in Maros Regency and have obtained permits at the Maros Investment and One-Stop Service Office which was obtained by 40 respondents. Primary data from this study was obtained from research instruments in the form of answers from questionnaires that were distributed online by using google forms to 40 respondents at Maros Link which was distributed containing 9 questions and for each question item there were 4 alternative answers that had been provided